2023
DOI: 10.1002/jso.27219
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic score from a multicentric retrospective analysis of patients affected by sarcoma with metachronous lung metastases undergoing metastasectomy

Abstract: Background Despite the lack of evidence‐based on prospective randomized studies, surgery has become the cornerstone of the treatment in patients with pulmonary oligometastatic sarcomas. Our study aimed to construct a composite prognostic score for metachronous oligometastatic sarcoma patients. Methods A retrospective analysis was performed on data patients who underwent radical surgery for metachronous metastases in six research institutes from January 2010 to December 2018. The log‐hazard ratio (HR) obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The findings revealed that uninsured and Medicaid-insured patients had higher mortality rates compared with privately insured patients. Finally, Gallina et al developed a prognostic score for patients with sarcoma and metachronous lung metastases who underwent metastasectomy and found that primary tumor size, histologic subtype, the number of lung metastases, and the presence of extrapulmonary metastases were associated with worse overall survival 44 .…”
Section: Soft-tissue Sarcoma Epidemiology and Outcomes Predictionmentioning
confidence: 99%
“…The findings revealed that uninsured and Medicaid-insured patients had higher mortality rates compared with privately insured patients. Finally, Gallina et al developed a prognostic score for patients with sarcoma and metachronous lung metastases who underwent metastasectomy and found that primary tumor size, histologic subtype, the number of lung metastases, and the presence of extrapulmonary metastases were associated with worse overall survival 44 .…”
Section: Soft-tissue Sarcoma Epidemiology and Outcomes Predictionmentioning
confidence: 99%